(untitled) (Latakia University Journal -Engineering Sciences Series, 2019)
In recent years, the problem of classifying objects in images has increased by using deep learning as a result of the industrial sector requirements. Despite of many algorithms used in this field, such as Deep Learning Neural Network DNN and Convolutional Neural Network CNN, the proposed systems to address this problem Lack of comprehensive solution to the difficulties of long training time and floating memory during the training process, low rating classification. Convolutional Neural Networks (CNNs), which are the most used algorithms for this task, were a mathematical pattern for analyzing images data. A new deep-traversal network pattern was proposed to solve the above problems. The aim of the research is to demonstrate the performance of the recognition system using CNNs networks on the available memory and training time by adapting appropriate variables for the bypass network. The database used in this research is CIFAR10, which consists of 60000 colorful images belonging to ten categories, as every 6,000 images are for a class of these items. Where there are 50,000 training images and 10,000 test tubes. When tested on a sample of selected images from the CIFAR10 database, the model achieved a rating classification of 98.87%. في السنوات الأخيرة نمت مشكلة تصنيف الكائنات في الصّور نتيجة لمتطلبات القطاع الصناعي.على الرّغم من تعدد التقنيات المستخدمة للمساعدة في عملية التصنيف SIFT Scale Invariant Feature Transforms، ORB Oriented Fast And Rotated Brief , SURF Speed Up Robust Features، إضافة لشبكات التعلم العميق Deep Learning Neural Network DNN والشبكات العصبونية الالتفافية Convolutional Neural Network CNN، فإن الأنظمة المقترحة لمعالجة هذه المشكلة تفتقر للحل الشّامل للصعوبات المتمثلة بوقت التّدريب الطّويل والذاكرة العائمة أثناء عملية التدريب، وانخفاض معدّل التصنيف. تعتبر الشبكات العصبونية الالتفافيةConvolutional Neural Networks (CNNs) من أكثر الخوارزميات استخداما لهذه المهمة، فقد كانت نموذجا حسابيا لتحليل البيانات الموجودة في الصور. تم اقتراح نموذج شبكة التفافية عميقة جديد لحل المشاكل المذكورة أعلاه. يهدف البحث إلى إظهار أداء نظام التّعرف باستخدام شبكاتCNNs على الذّاكرة المتاحة وزمن التدريب وذلك من خلال منهجة متغيرات مناسبة للشبكة العصبونية الالتفافية. قاعدة البيانات المستخدمة في هذا البحث هي CIFAR10 المكونة من60000 صورة ملونة تنتسب لعشرة أصناف، حيث أن كل 6000 صورة تكون لصنف من هذه الأصناف. يوجد 50000 صورة للتدريب و 10000 صورة للاختبار. حقق النموذج لدى اختباره على عينة من الصور المنتقاة من قاعدة البيانات CIFAR10 معدل تصنيف 98.87%، .